Editorial preface - Rosa Anna La Rocca (TeMA: Journal of Land Use, Mobility and Environment, 2024)
This Special Issue of TeMA - Journal of Land Use, Mobility and Environment proposes to delve into the concept of transition applied to urban and territorial systems with the aim of verifying the state of the art in scientific as well as in technical sector, also considering the effects of Covid-19pandemic crisis  (Angiello, 2021). What is urgent is the need to change both social behaviors and the use of primary resources (water, energy and soil) which is claimed by technicians and scholars as the only solution to face environmental challenges affecting nowadays cities. These challenges and the linked risks are so relevant that an in-depth change in the operative actions as well as in the theoretical approaches has become mandatory, in order to avoid negative and disruptive effects.  with this Special Issue we intended to draw the attention of technicians and scholars to the theme of urban transition which from many quarters seems to prefer the "ecological dimension" to pursue sustainability objectives. The eleven contributions received, while maintaining the underlying theme of the main theme, propose differentiated perspectives of sustainable transition which can be divided into three groups: